Discrete Modeling of Resonant Converters Practical Validation - Stahl, Jürgen; Dürbaum, Thomas (PCIM Conference, May 2012, 2012)
Discrete modeling is a fast and accurate method for describing resonant switch mode power converters. This paper applies discrete modeling onto resonant converters. It shows how to calculate the steady state, and shows as well the small signal control-to-output transfer function as the most important transfer function. Furthermore, the practical relevance of this model is investigated by comparing the calculated results with measurements, and an excellent agreement between theory and practice shows the accuracy of this modeling technique. A great emphasis is placed on the practical set-up, including the controller design, and measurements of the control- to-output transfer function. © VDE Verlag GMBH - Berlin.
UnivIS-Import:2015-03-09:Pub.2012.tech.IE.lselek.discre_7